Resin composition and its uses

The resin composition, with a specific blend of butene polymer, high-pressure low-density polyethylene, and ethylene-α-olefin copolymer, addresses the challenge of balancing heat seal strength and easy peelability in sealant films, resulting in films with improved peeling properties and appearance.

JP7671176B2Active Publication Date: 2025-05-01MITSUI CHEMICALS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021082128
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-14
Publication Date
2025-05-01
Estimated Expiration
2041-05-14

AI Technical Summary

Technical Problem

Existing sealant films struggle to balance heat seal strength and easy peelability, often resulting in a deteriorated peeling appearance due to residual thread-like resin.

Method used

A resin composition comprising 5-30% by mass of a specific butene polymer, 42-90% by mass of high-pressure low-density polyethylene, and 3-38% by mass of ethylene-α-olefin copolymer, with a mass ratio of high-pressure low-density polyethylene to ethylene-α-olefin copolymer ranging from 60/40 to 93/7, to achieve improved interface strength and peeling properties.

Benefits of technology

The solution enables sealant films and laminated films that protect contents with low heat seal strength for easy peelability, while maintaining a good appearance of the peeling surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671176000001
    Figure 0007671176000001
  • Figure 0007671176000002
    Figure 0007671176000002
  • Figure 0007671176000003
    Figure 0007671176000003
Patent Text Reader

Abstract

To provide: a sealant film and a laminated film having heat seal strength that is, while being able to protect a content, low to a degree where an easy-peel-property required in a market can be exhibited and having good appearance of a peeling surface; and a material thereof.SOLUTION: A resin composition comprises: 5 to 30 mass% of a butene-based polymer (A) that satisfies following (a-1) to (a-3); 42 to 90 mass% of high-pressure process low-density polyethylene (B); and 3 to 38 mass% of an ethylene / α-olefin copolymer (C) that satisfies the following (c-1) (where a total of (A), (B), and (C) is taken as 100 mass%), where a mass ratio of the high-pressure process low-density polyethylene (B) to the ethylene / α-olefin copolymer (C) is 60 / 40 to 93 / 7: (a-1) a ratio of a weight average molecular weight Mw to a number average molecular weight Mn (Mw / Mn) is 5-20; (a-2) a melting point as measured by DSC is 100 to 130°C; (a-3) an MFR (190°C, 2.16 kg load) is 0.3 to 10 g / 10 min.; and (c-1) an MFR (190°C, 2.16 kg load) is 0.1 to 16 g / 10 min.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and uses thereof, and more particularly to a resin composition suitable as a raw material for a sealant film, as well as a sealant film and a laminate film using the sealant film. [Background technology]

[0002] A sealant film with easy peelability used for container packaging is required to simultaneously satisfy the conflicting properties of hermeticity and easy peelability. Of these, with regard to hermeticity, it is required to have a heat seal strength at least sufficient to always protect the contents, and to have a small temperature dependency of the heat seal strength so as to be compatible with a wide variety of substrates. On the other hand, with regard to easy peelability, it is required to be heat sealed to an extent that it can be easily peeled by hand.

[0003] Patent Document 1 discloses a composition containing a butene polymer having a proportion of components having a molecular weight of 10,000 or less of 2% or more, a melting point of 100 to 130°C, and an MFR of 0.3 to 10 g / 10 min, and an ethylene polymer, in which the ethylene polymer contains 90 to 40 mass% of high-pressure low-density polyethylene and 10 to 60 mass% of an ethylene-α-olefin copolymer (the total amount of the ethylene polymers is taken as 100 mass%). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-123842 A Summary of the Invention [Problem to be solved by the invention]

[0005] There is a demand in the market for a sealant film that is easier to peel off than the sealant film produced from the composition. However, for example, in the composition described in Patent Document 1, when the compounding ratio of the butene polymer is increased to lower the heat seal strength, thread-like resin remains on the peeling surface of the sealant film, resulting in a poor peeling appearance.

[0006] The present invention aims to provide a sealant film and laminate film that are capable of protecting the contents, have a low heat seal strength that allows them to exhibit the easy peel property required in the market, and have a good appearance on the peeled surface, as well as materials for the same. [Means for solving the problem]

[0007] As a result of the inventor's research, it has been found that the above-mentioned problems can be solved by the following configuration example. In this specification, the numerical range "A to B" indicates A or more and B or less.

[0008] [1] 5 to 30 mass% of a butene polymer (A) satisfying the requirements (a-1), (a-2), and (a-3), 42 to 90% by mass of high-pressure low-density polyethylene (B), The composition contains 3 to 38% by mass of an ethylene-α-olefin copolymer (C) satisfying requirement (c-1) (wherein the total of the butene polymer (A), the high-pressure low-density polyethylene (B) and the ethylene-α-olefin copolymer (C) is taken as 100% by mass), A resin composition characterized in that the mass ratio of the high-pressure low-density polyethylene (B) to the ethylene-α-olefin copolymer (C) [(B) / (C)] is 60 / 40 to 93 / 7. (a-1): The ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn measured by the GPC method is 5 to 20. (a-2): The melting point measured by a differential scanning calorimeter is 100 to 130°C. (a-3): The melt flow rate (190°C, 2.16 kg load) is 0.3 to 10 g / 10 min. (c-1): The melt flow rate (190°C, 2.16 kg load) is 0.1 to 16 g / 10 min.

[0009] [2] The resin composition according to [1], wherein the butene polymer (A) further satisfies the requirement (a-4). (a-4): The proportion of components having a molecular weight of 10,000 or less, as determined from an integrated molecular weight distribution curve obtained by measurement using a GPC method, is 2% or more.

[0010] [3] The resin composition according to [1] or [2], wherein the butene polymer (A) further satisfies the requirement (a-5). (a-5): Comprises 90 to 100 mol % of the structural unit (i) derived from 1-butene and the structural unit (ii) derived from an α-olefin having 2 to 10 carbon atoms (excluding 1-butene) as 100 mol % in total, and comprises 90 to 100 mol % of the structural unit (i) and 0 to 10 mol % of the structural unit (ii).

[0011] [4] The resin composition according to any one of claims [1] to [3], wherein the ethylene / α-olefin copolymer (C) satisfies the requirement (c-2). (c-2): Density is 870-936kg / m 3 It is.

[0012] [5] A film made of the resin composition according to any one of [1] to [4].

[0013] [6] A laminated film obtained by laminating the film according to [5] above with another layer.

[0014] [7] A laminated film according to [6], comprising a sealant layer and a base layer laminated together, the sealant layer being made of the film of [5].

[0015] [8] A laminated film according to [6], comprising a sealant layer, an intermediate layer and a base layer laminated in this order, the sealant layer being made of an ethylene-based polymer, and the intermediate layer being made of the film of [5]. Effect of the Invention

[0016] According to the present invention, it is possible to provide a sealant film and a laminate film, as well as materials thereof, which are capable of protecting the contents, have a low heat seal strength so as to exhibit the easy peel property required in the market, and have a good appearance on the peel surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] ≪Resin composition≫ The resin composition according to the present invention (hereinafter also referred to as "the composition") contains 5 to 30 mass% of a specific butene polymer (A), 42 to 90 mass% of a high-pressure low-density polyethylene (B), and 3 to 38 mass% of a specific ethylene-α-olefin copolymer (C) (the total of (A), (B), and (C) is taken as 100 mass%), and satisfies the following requirement (X):

[0018] [Requirement (X)] The mass ratio of the high-pressure low-density polyethylene (B) to the ethylene-α-olefin copolymer (C) [(B) / (C)] is 60 / 40 to 93 / 7, preferably 70 / 30 to 92 / 8, and more preferably 75 / 25 to 90 / 10. When the mass ratio of the high-pressure low-density polyethylene (B) to the ethylene-α-olefin copolymer (C) is 93 / 7 or less, when the present composition is used as a sealant film, thread-like resin is unlikely to remain on the peeled surface of the sealant film, and the appearance of the peeled surface is good, which is preferable. It is presumed that the reason why the appearance of the peeled surface is good when the mass ratio [(B) / (C)] is 93 / 7 or less is because the interfacial strength between the high-pressure low-density polyethylene (B) and the butene polymer (A) is improved. That is, it is presumed that the interfacial strength between the high-pressure low-density polyethylene (B) and the butene polymer (A) is improved, so that the butene polymer (A) peels off from the high-pressure low-density polyethylene (B) only in the vicinity of the peeled surface, and as a result, the butene polymer (A) is unlikely to remain on the peeled surface. On the other hand, when the appearance of the peeled surface is not good, it is presumed that the butene polymer (A) peels off from the high-pressure low-density polyethylene (B) even in areas other than the vicinity of the peeled surface, and the butene polymer (A) at a position relatively distant from the peeled surface remains on the peeled surface connected to the butene polymer (A) in the vicinity of the peeled surface, causing stringiness on the peeled surface. The mass ratio [(B) / (C)] of 60 / 40 or more is preferable because the heat seal strength is low. The reason why the above effect is obtained when the mass ratio [(B) / (C)] is 60 / 40 or more is presumed to be because the material strength is low when the composition adjusted to the mass ratio is used as a sealant.

[0019] The content of the butene polymer (A) in the composition is 5 to 30 mass%, preferably 8.5 to 30 mass%, and more preferably 10 to 30 mass% (wherein the total of the butene polymer (A), high-pressure low-density polyethylene (B) and ethylene-α-olefin copolymer (C) is taken as 100 mass%). The content of the butene polymer (A) within the above range is preferable since the heat seal strength is low.

[0020] <Butene polymer (A)> Examples of the butene polymer (A) include a homopolymer of 1-butene and a copolymer of 1-butene and an α-olefin having 2 to 10 carbon atoms other than 1-butene. The butene polymer (A) used in the present composition may be one type or two or more types.

[0021] Examples of the α-olefin include ethylene, propylene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, and 4,4-dimethyl-1-hexene. Preferred are ethylene, propylene, 1-hexene, 4-methyl-1-pentene, and 1-octene, and more preferred are ethylene and propylene.

[0022] The butene polymer (A) may be copolymerized with a small amount of other comonomer as required, within the scope of not impairing the effects of the present invention. The other comonomer is a monomer other than 1-butene and the α-olefin, and is copolymerizable with at least one of 1-butene and the α-olefin. The other comonomer may be a monomer copolymerizable with both 1-butene and the α-olefin. The butene polymer (A) preferably has a 1-butene content of 90 to 100 mol %, as described in detail in the following requirement (a-5), and typically has an α-olefin content of 0 to 10 mol % (where the total of the 1-butene content and the α-olefin content is 100 mol %).

[0023] The butene polymer (A) satisfies the following requirements (a-1) to (a-3).

[0024] [Requirement (a-1)] The ratio of weight average molecular weight Mw to number average molecular weight Mn, i.e., Mw / Mn, measured by a gel permeation chromatography (GPC) method (polystyrene equivalent) under conditions employed in the examples described below is 5 to 20, preferably 5 to 10, and more preferably 6 to 9. If the Mw / Mn is within this range, the dispersibility when kneaded with the ethylene polymer is improved, and therefore the peelability is improved. In adjusting Mw / Mn, for example, two or more kinds of butene polymers differing in one or more of weight average molecular weight Mw, number average molecular weight Mn, or Mw / Mn are prepared and mixed together, thereby increasing Mw / Mn.

[0025] [Requirement (a-2)] The melting point measured by a differential scanning calorimeter under the conditions employed in the examples described below is 100 to 130°C, preferably 105 to 130°C, and more preferably 110 to 125°C. A melting point within this range improves the heat resistance of the film, making it suitable for packaging that involves boiling or retort sterilization, and also allows for heat sealing over a wide range of sealing temperatures.

[0026] [Requirement (a-3)] The melt flow rate (ASTM D-1238, 190° C., 2.16 kg load) is 0.3 to 10 g / 10 minutes, preferably 1.2 to 8 g / 10 minutes, and more preferably 2 to 5 g / 10 minutes. It is preferable that the melt flow rate is within this range, since the resin composition of the present invention can be molded into a film at a high molding speed using an existing molding machine.

[0027] The butene polymer (A) has a ratio of weight-average molecular weight Mw to number-average molecular weight Mn, a melting point, and a melt flow rate within specific ranges, and therefore has an excellent balance of dispersibility and easy peelability when kneaded with an ethylene polymer. In other words, it is presumed that by blending a butene polymer (A) satisfying the requirements (a-1) to (a-3), a film obtained from the composition can achieve low heat seal strength over a wide range of sealing temperatures.

[0028] The butene polymer (A) may satisfy one or more of the following requirements (a-4) to (a-6), and preferably satisfies the following requirements (a-4) and (a-5).

[0029] [Requirement (a-4)] The proportion of components having a molecular weight of 10,000 or less, as determined from an integral molecular weight distribution curve obtained by a gel permeation (GPC) method (polystyrene equivalent), is preferably 2% or more, more preferably 2.5% or more. The upper limit of the proportion of components having a molecular weight of 10,000 or less is determined mainly depending on the requirements (a-1) and (a-3), but is preferably 5% or less. The conditions for measurement by the GPC method are the conditions described in the examples below.

[0030] If the ratio is within this range, the dispersibility when kneaded with the ethylene polymer is improved, and therefore the peelability is improved. The ratio can be increased, for example, by polymerizing a low molecular weight butene polymer in one step of a multi-stage polymerization process, or by melt-kneading a low molecular weight butene polymer.

[0031] [Requirement (a-5)] The butene polymer (A) has a 1-butene content of usually 90 to 100 mol%, preferably 95 to 100 mol%, and more preferably 98 to 100 mol%, and an α-olefin content of 0 to 10 mol%, preferably 0 to 5 mol%, and more preferably 0 to 2 mol% (the total of the 1-butene content and the α-olefin content is 100 mol%).

[0032] [Requirement (a-6)] The density measured under the conditions employed in the examples described below is 880 to 925 kg / m 3 , preferably 885 to 920 kg / m 3 When the density of the butene polymer (A) is within this range, the friction coefficient of the surface of a film formed from the resin composition is small, and therefore, when a container is finally produced from the film, it is possible to fill the container with the contents at a high filling speed.

[0033] [Method for producing butene polymer (A)] Examples of the method for producing the butene polymer (A) include the methods described in International Publication No. 2002 / 002659, etc. On pages 32-33 of this patent document, the following (M1) and (M2) are described as examples of the method for producing the solid titanium catalyst (A') used in the production of the butene copolymer. (M1) contacting a halogen-containing magnesium compound (α) with a solubilizing agent (β) capable of dissolving the halogen-containing magnesium compound (α) in a solvent (γ) to obtain a solution (I); A first compound (δ) having two or more ether bonds present via a plurality of atoms is added to the solution (I) to obtain a solution (II); A method in which a liquid titanium compound (ε) is brought into contact with the solution (II) to obtain a solution (III), or a solid is further separated from the solution (III). (M2) contacting a halogen-containing magnesium compound (α) with a solubilizing agent (β) capable of dissolving the halogen-containing magnesium compound (α) in a solvent (γ) to obtain a solution (I); A first compound (δ) having two or more ether bonds present via a plurality of atoms is added to the solution (I) to obtain a solution (II); contacting the solution (II) with a liquid titanium compound (ε) to obtain a solution (III); A method in which a second compound (δ') having two or more ether bonds present via a plurality of atoms is added to the solution (III) to obtain a solution (IV), or further a solid is separated from the solution (IV). In the present invention, from the viewpoint of producing a butene polymer (A) having a high ratio of components having a molecular weight of 10,000 or less, a butene polymer (A) is preferably produced by (co)polymerizing 1-butene in the presence of a solid titanium catalyst (A') produced by the method (M1) (i.e., a method not including a step of adding a second compound (δ') having two or more ether bonds present via a plurality of atoms to the solution (III) to obtain a solution (IV) or a step of separating a solid from the solution (IV)).

[0034] Alternatively, two or more kinds of butene polymers (each of which may or may not satisfy all of the requirements (a-1) to (a-3)) may be prepared and mixed to prepare the butene polymer (A) so that the overall mixture satisfies the requirements (a-1) to (a-3).

[0035] <High-pressure low-density polyethylene (B)> The melt flow rate of the high pressure low density polyethylene (B) (ASTM D-1238, 190°C, 2.16 kg load) is preferably 0.2 to 30 g / 10 min, more preferably 0.5 to 10 g / 10 min, and even more preferably 0.8 to 8 g / 10 min. If the melt flow rate is within this range, the composition can be molded into a film at a high molding speed using an existing molding machine.

[0036] The density of high-pressure low-density polyethylene (B) is usually 900 to 940 kg / m 3 , preferably 910 to 930 kg / m 3 It is.

[0037] As the high-pressure low-density polyethylene (B), for example, NUC8160 (MFR = 2.4 g / 10 min, density = 922 kg / m 3 (manufactured by ENEOS NUC Corporation).

[0038] <Ethylene-α-olefin copolymer (C)> Examples of the ethylene-α-olefin copolymer (C) include ethylene-α-olefin random copolymers. The α-olefin is an α-olefin having 3 to 20 carbon atoms, preferably 3 to 10 carbon atoms, and examples thereof include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, and 4,4-dimethyl-1-hexene. These may be used alone or in combination of two or more. In addition, the ethylene-α-olefin copolymer (C) may be one in which a small amount of comonomer other than ethylene and α-olefin is further polymerized as necessary.

[0039] The α-olefin content of the ethylene / α-olefin copolymer (C) is preferably 0.1 to 15 mol %, more preferably 0.5 to 10 mol %, provided that the total of the ethylene content and the α-olefin content is 100 mol %.

[0040] The ethylene / α-olefin copolymer (C) satisfies the following requirement (c-1), and preferably satisfies the following requirements (c-1) and (c-2).

[0041] [Requirement (c-1)] The melt flow rate of the ethylene / α-olefin copolymer (C) (ASTM D-1238, 190°C, 2.16 kg load) is 0.1 to 16 g / 10 min, preferably 0.5 to 9 g / 10 min, and more preferably 0.5 to 3.5 g / 10 min. When an ethylene / α-olefin copolymer (C) having a melt flow rate within the above range is used, the dispersibility of the butene copolymer (A) is improved, and therefore the ease of peeling is improved, so that the heat seal strength of the sealant film obtained from this composition is low and the appearance of the peeled surface is good.

[0042] [Requirement (c-2)] The density of the ethylene-α-olefin copolymer (C) is usually 870 to 936 kg / m 3and preferably 885 to 932 kg / m 3 and more preferably 912 to 927 kg / m 3 It is preferable that the density of the ethylene-α-olefin copolymer (C) is within this range, since a film having excellent transparency and low-temperature sealability can be obtained. When the ethylene-α-olefin copolymer (C) having a density within the above range is used, the interfacial strength between the high-pressure low-density polyethylene (B) and the butene polymer (A) is improved to a level that allows good peel appearance, and the seal strength does not become too high. Therefore, the sealant film obtained from this composition has low heat seal strength and good peel appearance.

[0043] An example of the ethylene-α-olefin copolymer (C) is the commercially available Evolue SP2510 (MFR=1.5g / 10min, density 923kg / m 3 , manufactured by Prime Polymer Co., Ltd.), Evolue SP2540 (MFR = 3.8 g / 10 min, density 924 kg / m 3 , manufactured by Prime Polymer Co., Ltd.), Evolue SP1510 (MFR = 1.0 g / 10 min, density 915 kg / m 3 (manufactured by Prime Polymer Co., Ltd.).

[0044] <Various additives> The composition may contain any additives, such as antioxidants, heat stabilizers, weather stabilizers, antifogging agents, antiblocking agents, slip agents, lubricants, crystal nucleating agents, antistatic agents, flame retardants, pigments, dyes, fillers, etc., within the range that does not impair the effects of the present invention (for example, a total of 1 mass % or less in the composition).

[0045] <Method of manufacturing the present composition> The composition can be prepared by mixing the butene polymer (A), the high-pressure low-density polyethylene (B), the ethylene-α-olefin copolymer (C), and optionally various additives by a conventionally known method.

[0046] <Films and laminated films> The film according to the present invention is made of the composition and is preferably used as a sealant film for packaging materials.

[0047] The thickness of the film is appropriately set depending on the application of the film, and is preferably 3 to 100 μm when used as a sealant film, for example. The film according to the present invention can be produced by molding the resin composition according to the present invention. Examples of the film molding method include cast molding and inflation molding. The temperature of the molten resin during film molding is preferably 160 to 260°C.

[0048] The laminate film according to the present invention is formed by laminating the above-mentioned film according to the present invention with other layers. Examples of the laminate film according to the present invention include the following two types. (i) A laminated film in which a sealant layer and a base layer are laminated together, the sealant layer being made of the film (sealant film) according to the present invention. (ii) A laminated film comprising a sealant layer, an intermediate layer and a base layer laminated in this order, the sealant layer comprising an ethylene-based polymer, and the intermediate layer comprising the film according to the present invention.

[0049] In the laminated film according to the present invention, when the film according to the present invention is used as an intermediate layer as in the laminated film (ii), the peeling start portion of the laminated film is between the sealant layer and the object sealed with the laminated film (sealed object), but since the destruction between the layers immediately moves to between the sealant layer and the intermediate layer, the intermediate layer is substantially peeled off from the sealant layer. In other words, the peeling surface is between the sealant layer and the intermediate layer, and the sealant layer is not substantially peeled off from the sealed object.

[0050] When the adhesive strength between the layers of the laminated film is insufficient, an adhesive layer may be provided between the layers. The laminated film is preferably used as a packaging film or a packaging sheet, and may also be used as a container material or a container lid material.

[0051] Examples of the substrate layer include polyolefin films such as polyethylene or polypropylene, styrene-based resin films, polyester films such as polyethylene terephthalate or polybutylene terephthalate, polyamide films such as nylon 6 or nylon 6,6, laminated films of polyolefin films and resin films having gas barrier properties such as polyamide resins or ethylene-vinyl alcohol copolymer resins, metal foils such as aluminum, vapor-deposited films on which aluminum, silica, etc. are vapor-deposited, paper, etc. The substrate layer is appropriately selected depending on the purpose of use of the packaging material, etc., and may be used alone or in a laminate of two or more types.

[0052] Examples of the method for producing the laminated film include the following (M11) to (M13). (M11) A method in which the raw resins for the sealant layer, the raw resins for the base layer, and optionally the raw resins for the intermediate layer are each fed into separate extruders, melted, merged, laminated, and extruded into a sheet from a T-die (co-extrusion method). (M12) A method in which the raw resins for the sealant layer are fed into an extruder and melt-extruded onto a prefabricated base layer, or onto an intermediate layer of a laminate consisting of a prefabricated base layer and intermediate layer, thereby laminating the resin (melt lamination method). (M13) A method in which a sealant layer, a base material layer and an optional intermediate layer are each made from the corresponding raw material resins, and these are thermocompressed together using a group of heated rolls or the like (thermal lamination method). Of these methods, the coextrusion method (M11) is preferred because it requires a short production time and provides good adhesion between layers.

[0053] The sealing temperature when the film or laminated film of the present invention is heat-sealed is usually 100 to 180° C., and preferably 140 to 170° C. The sealing pressure is usually 0.1 to 0.5 MPa.

[0054] When this sealant film (sealant layer) is layered on another film and a heat sealing operation is performed, or when this sealant film (sealant layer) is layered on another film and a heat sealing operation is performed, the layered films are firmly bonded to each other by the adhesive force of the sealant film (sealant layer), and can be separated from each other with a moderate force. Therefore, the film and laminated film of the present invention can be used as a film that has both heat sealability and easy peelability.

[0055] When the laminated film according to the present invention is a laminated film (ii) in which a sealant layer, an intermediate layer and a base layer are laminated in this order, the sealant layer is made of an ethylene-based polymer and the intermediate layer is made of the film according to the present invention, an example of the raw material for the sealant layer is polyethylene. Examples of polyethylene usable as the raw material for the sealant layer include high-pressure low-density polyethylene and a mixture of high-pressure low-density polyethylene and ethylene-α-olefin copolymer, and the mass ratio of these two resins is, for example, high-pressure low-density polyethylene:ethylene-α-olefin copolymer=1:0 to 70:30.

[0056] The density of the ethylene-α-olefin copolymer that can be used as the raw material for the sealant layer in the laminated film (ii) is preferably 870 to 920 kg / m 3 , more preferably 880 to 905 kg / m 3 In particular, by blending a low-density ethylene-α-olefin copolymer, the heat sealability at low temperatures is improved, and the suitability for high-speed sealing (productivity) is enhanced. The melt flow rate (190°C, 2.16 kg load) of the ethylene-α-olefin copolymer usable as a raw material for the sealant layer in the laminated film (ii) is preferably 0.5 to 7.0 g / 10 min, more preferably 1.0 to 4.0 g / 10 min. Examples of ethylene-α-olefin usable as a raw material for the sealant layer include, in addition to the copolymers listed as the ethylene-α-olefin copolymer (C), TAFMER A-1085S (MFR=1.2 g / 10 min, density=885 kg / m 3and Mitsui Chemicals, Inc.

[0057] A sealed container, for example a bag-like container, can be produced by preparing two laminated films according to the present invention and arranging the sealant layers facing each other, or folding the laminated film according to the present invention so that the sealant layers face each other, or arranging the sealant layer of the laminated film according to the present invention and another film, and then heat-sealing the periphery from the outer surface side of either one of them to form a desired container shape. If this bag-like container forming process is combined with a content filling process, the bottom and sides of the bag-like container can be heat-sealed, the contents can be filled, and then the top can be heat-sealed to automatically complete the package. Therefore, this laminated film can be supplied to an automatic packaging device for solid, powder, or liquid materials such as snacks.

[0058] Alternatively, the laminate film according to the present invention or other films may be molded into a cup-shaped container shape by vacuum forming, deep drawing, or other means, or a normal injection-molded container may be prepared, and the container may be filled with contents. The laminate film or other films may then be used as a lid to cover the container, and the container may be heat-sealed along the periphery of the top or side of the container to obtain a package containing the contents. In this case, the sealant film according to the present invention may be used as the sealant layer of the lid, the sealant layer of the container body, or both. This container may be suitably used for packaging instant ramen, miso paste, ham, bacon, jelly, pudding, snacks, and the like.

[0059] The structure and manufacturing method of the container are not limited to the above description and can be changed arbitrarily. Other films or containers that can be used in combination with the film or laminated film of the present invention include packaging materials molded from conventional resins such as polyethylene, ethylene-vinyl acetate copolymer, and polypropylene. For example, such materials can be molded into a container-shaped molded body having a brim at the opening, laminated so that the sealant layer surface is overlapped on the brim at the opening, and the two surfaces can be joined by heat sealing to form a container package. The sealant film or sealant layer and the packaging material can be heat-sealed with sufficient adhesive strength, and can be easily opened because they have easy peelability. Therefore, this container can be suitably used as a packaging container that has airtightness and easy peelability, especially in the field of food packaging. EXAMPLES

[0060] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0061] [Molecular weight distribution (Mw / Mn), percentage of components with molecular weights of 10,000 or less] The measurements were performed using a gel permeation chromatograph HLC-8321 GPC / HT model manufactured by Tosoh Corporation, as follows. The separation columns were two TSKgel GMH6-HT and two TSKgel GMH6-HTL, each with an inner diameter of 7.5 mm and a length of 300 mm, and the column temperature was set to 140°C. Orthodichlorobenzene (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the mobile phase, and 0.025 wt% BHT (manufactured by Wako Pure Chemical Industries, Ltd.) was used as the antioxidant, and the flow rate was set to 1.0 mL / min. The sample concentration was set to 30 mg / 20 mL, the sample injection amount was set to 0.4 mL, and a differential refractometer was used as the detector. 16 TSK standard polystyrenes manufactured by Tosoh Corporation were used as standard samples. For molecular weight calculations, data processing software Empower3 manufactured by Waters was used to calculate the weight average molecular weight Mw, number average molecular weight Mn, molecular weight distribution (Mw / Mn), and the proportion of components with a molecular weight of 10,000 or less.

[0062] [Measurement of ethylene content in 1-butene-ethylene copolymer] The measurements were carried out using an AVANCEIII500 (CryoProbe) NMR measuring device manufactured by Bruker Biospin Corporation as follows.

[0063] 60 mg of sample and 0.5 ml of orthodichlorobenzene were placed in a 5 mm inner diameter NMR tube and dissolved by heating. 0.1 ml of deuterated benzene was added to this solution and heated at 120°C. 13 C-NMR measurements were performed. The number of accumulations was set to 128 or more. 13 The compositions of 1-butene and ethylene were quantified by C-NMR spectroscopy.

[0064] [Melting point] A polymer containing a 1-butene-derived structural unit was molded under the following press molding conditions, and the obtained 1 mm-thick press sheet was stored at room temperature for 10 days to be used as a sample. The melting point of the sample was measured by a differential scanning calorimeter (DSC) under the DSC measurement conditions described below.

[0065] [Press molding conditions] Press machine: Kansai Roll Co., Ltd. (Model number: PEWE-70 / 50 35) Heating time: 5 minutes Heating temperature: 200℃ Pressure during heating: 5MPa Cooling rate: 40℃ / min or more (pressurize at 5MPa for 4 minutes using another press set at 30℃, then cool to room temperature)

[0066] [DSC measurement conditions] Using PerkinElmer's DSC Pyris1 or DSC7, approximately 5 mg of sample was heated from room temperature to 200°C at 10°C / min under a nitrogen atmosphere (20 ml / min), and the largest crystal melting peak was taken as the melting point.

[0067] [density] A 1 mm thick press sheet was produced under the same conditions as in the melting point measurement, and after storing it at room temperature for 10 days, the density was measured according to a measurement method in accordance with ASTM D-1505-68.

[0068] [Melt flow rate (MFR)] The measurements were carried out in accordance with ASTM D-1238 at 190°C under a load of 2.16 kg.

[0069] [Preparation Example] Preparation of butene polymer (BER-1) A solid titanium catalyst component was prepared by the manufacturing method described in JP 2019-123842 A. Using the obtained solid titanium catalyst component, 1-butene and ethylene were copolymerized by a method according to the manufacturing method described in JP 2019-123842 A, while appropriately changing the supply amounts of 1-butene, ethylene, and hydrogen, to obtain a butene polymer (BER-1). The physical properties of the polymer BER-1 are shown in Table 1.

[0070] [Table 1]

[0071] <Ingredients> The raw materials used in the following examples and comparative examples are as follows.

[0072] [Butene polymer (A)] · "BER-1": The polymer BER-1 prepared in the above Preparation Example was used as the butene polymer (A).

[0073] [High-pressure low-density polyethylene (B)] "LDPE-1": NUC8160 (ENEOS NUC Corporation), MFR (190°C, 2.16 kg load) = 2.4 g / 10 min, density = 922 kg / m 3

[0074] [Ethylene-α-olefin copolymer (C)] "LLDPE-1": Ultzeex 2022L (Prime Polymer Co., Ltd.), MFR (190°C, 2.16 kg load) = 2.0 g / 10 min, density 919 kg / m 3 "LLDPE-2": Evolue SP2510 (Prime Polymer Co., Ltd.), MFR (190°C, 2.16 kg load) = 1.5 g / 10 min, density 923 kg / m 3 "LLDPE-3": Evolue SP2540 (Prime Polymer Co., Ltd.), MFR (190°C, 2.16 kg load) = 3.8 g / 10 min, density 924 kg / m 3 "LLDPE-4": Evolue SP1510 (Prime Polymer Co., Ltd.), MFR (190°C, 2.16 kg load) = 1.0 g / 10 min, density 915 kg / m 3 "LLDPE-5": Evolue SP1540 (Prime Polymer Co., Ltd.), MFR (190°C, 2.16 kg load) = 3.8 g / 10 min, density 913 kg / m 3 "LLDPE-6": Evolue SP1071C (Prime Polymer Co., Ltd.), MFR (190°C, 2.16 kg load) = 10 g / 10 min, density 910 kg / m 3 "EBR-1": A-1085S (Mitsui Chemicals, Inc.), MFR (190°C, 2.16 kg load) = 1.2 g / 10 min, density 885 kg / m 3 "EBR-2": A-4085S (Mitsui Chemicals, Inc.), MFR (190°C, 2.16 kg load) = 3.6 g / 10 min, density 885 kg / m 3

[0075] [Other copolymers] "EBR-3": A-20085S (Mitsui Chemicals, Inc.), MFR (190°C, 2.16 kg load) = 18 g / 10 min, density 885 kg / m 3

[0076] [Example 1] [Production of Laminated Film] A two-layer T-die cast molding machine with a die width of 300 mm, equipped with an extruder with a screw diameter of 40 mm for molding the base layer and an extruder with a screw diameter of 30 mm for molding the sealant layer, was used to produce a film using the following resin composition for each layer under the following molding conditions. That is, a laminated film was produced in which the sealant layer and the base layer were laminated using a sealant film molded from this composition as the sealant layer.

[0077] (Resin Composition for Producing Each Layer) ·Base material layer: A resin composition obtained by blending 50 parts by mass each of LDPE-1 and LLDPE-1. Sealant layer: A resin composition obtained by blending 20 parts by mass of BER-1 as a butene polymer (A), 70 parts by mass of LDPE-1 as a high-pressure low-density polyethylene (B), and 10 parts by mass of LLDPE-2 as an ethylene-α-olefin copolymer (C).

[0078] (Molding conditions) Film forming temperature: 230℃ Chill roll temperature: 30℃ Film composition: Base layer / sealant layer (50μm / 20μm) Film forming speed: 10m / min

[0079] [Measurement of heat seal strength] Two laminated films molded in Example 1 were stacked with the sealant layers facing each other, with the MD directions (the direction in which the molten resin was flowed during molding) of the sealant layers aligned, and both sides of the stacked films were sandwiched between 50 μm thick Teflon (registered trademark) sheets to prepare a test specimen. Next, the heat seal bar of a heat seal tester (manufactured by Tester Sangyo Co., Ltd., TP-701-G type) was set to a width of 5 mm x length of 300 mm, and the lower heat seal bar was set to 70°C. The upper heat seal bar was set to 120°C, and the test specimen (Teflon sheet / laminated film / laminated film / Teflon sheet) was sandwiched between the seal bars and heat-sealed at a pressure of 0.2 MPa for 1.0 seconds. The Teflon sheets were removed, and the heat-sealed film portion was left at about 23°C for one day. After that, a 15 mm wide slit was made in the film to include the heat-sealed portion, and the unsealed portion was fixed to a tensile tester (Shimadzu Corporation, EZ-LX) and the peel strength of the film was measured at a speed of 300 mm / min. The above operation was repeated five times, and the average value was taken as the heat-seal strength. The maximum peel strength was used as the peel strength. The results are shown in Table 2. Similar experiments were carried out by changing the set temperature of the upper heat seal bar to 130° C., 140° C., 150° C., 160° C., 170° C., or 180° C. The results obtained at these set temperatures are also shown in Table 2.

[0080] [Seal strength evaluation] The heat seal strength was evaluated according to the following criteria. (Evaluation Criteria) ◯: When the heat sealing temperature is 140° C., the heat sealing strength is 1 N / 15 mm or more, and when the heat sealing temperature is 160° C., the heat sealing strength is 2 N / 15 mm or less. △: The heat seal strength is 1 N / 15 mm or more when the heat seal temperature is 140°C, and the heat seal strength is more than 2 N / 15 mm and 3 N / 15 mm or less when the heat seal temperature is 160°C. ×: When the heat sealing temperature is 140°C, the heat sealing strength is less than 1 N / 15 mm, or when the heat sealing temperature is 160°C, the heat sealing strength exceeds 3 N / 15 mm.

[0081] [Evaluation of stringiness] After the heat seal strength measurement, the sealed surface of the film sample was observed and evaluated according to the following criteria depending on whether or not thread-like resin had adhered to the sealed surface and its surroundings. The results are shown in Table 2. (Evaluation Criteria) ◯: No resin threads were observed on the sealing surface or around the sealing surface. △: Thread-like resin less than 1 mm long was attached to the sealing surface or around the sealing surface. ×: Thread-like resin having a length of 1 mm or more was attached to the sealing surface or the periphery of the sealing surface.

[0082] [Appearance Evaluation] The evaluation result of stringiness at 160°C was taken as the result of appearance evaluation.

[0083] 〔comprehensive evaluation〕 Based on the results of the seal strength evaluation and appearance evaluation, the following evaluation criteria were used. The results are shown in Table 2. (Evaluation Criteria) ◯: Both the seal strength evaluation and the appearance evaluation were ◯. Δ: At least one of the seal strength evaluation and the appearance evaluation was Δ, and no items were rated ×. ×: At least one of the seal strength evaluation and the appearance evaluation was ×.

[0084] [Examples 2 to 13, Comparative Examples 1 to 5] A laminated film was produced in the same manner as in Example 1, except that the resin composition shown in Table 2 was used as the resin composition for the sealant layer, and the heat seal strength and stringiness were evaluated by the same evaluation methods as in Example 1. The results are shown in Table 2. In some examples and comparative examples, the heat seal strength was not measured at 130°C, 150°C, and 170°C, and therefore the heat seal strength is indicated as "-". Under conditions where the heat seal strength was not measured, the evaluation of stringiness was also not performed, and therefore the evaluation result was indicated as "-".

[0085] [Table 2]

[0086] [Table 3]

Claims

1. a butene polymer (A) satisfying the requirements (a-1), (a-2), and (a-3) in an amount of 5 to 30% by mass; 42 to 90% by mass of high-pressure low-density polyethylene (B), The composition contains 3 to 38% by mass of an ethylene / α-olefin copolymer (C) satisfying requirement (c-1) (wherein the total of the butene polymer (A), the high-pressure low-density polyethylene (B), and the ethylene / α-olefin copolymer (C) is taken as 100% by mass), A resin composition characterized in that the mass ratio [(B) / (C)] of the high-pressure low-density polyethylene (B) and the ethylene / α-olefin copolymer (C) is 60 / 40 to 93 / 7. (a-1): The ratio Mw / Mn, which is the ratio of the weight average molecular weight Mw to the number average molecular weight Mn, measured by the GPC method, is 6 to 9. (a-2): The melting point measured by a differential scanning calorimeter is 100 to 130°C. (a-3): Melt flow rate (190°C, 2.16 kg load) is 2 to 10 g / 10 min. (c-1): Melt flow rate (190° C., 2.16 kg load) is 0.1 to 16 g / 10 min.

2. The resin composition according to claim 1, wherein the butene polymer (A) further satisfies the requirement (a-4). (a-4): The proportion of components having a molecular weight of 10,000 or less, as determined from an integrated molecular weight distribution curve obtained by measurement using a GPC method, is 2% or more.

3. The resin composition according to claim 1 or 2, wherein the butene polymer (A) further satisfies the requirement (a-5). (a-5): Comprises 90 to 100 mol % of the structural unit (i) derived from 1-butene and the structural unit (ii) derived from an α-olefin having 2 to 10 carbon atoms (excluding 1-butene), with the total of these units being 100 mol %.

4. The resin composition according to any one of claims 1 to 3, wherein the ethylene / α-olefin copolymer (C) satisfies the requirement (c-2). (c-2): Density is 870 to 936 kg / m 3 It is.

5. A film comprising the resin composition according to any one of claims 1 to 4.

6. A laminated film comprising the film according to claim 5 and another layer laminated thereto.

7. 7. The laminated film according to claim 6, which comprises a sealant layer and a substrate layer laminated together, the sealant layer being made of the film according to claim 5.

8. 7. The laminated film according to claim 6, which comprises a sealant layer, an intermediate layer and a base layer laminated in this order, said sealant layer being made of an ethylene-based polymer, and said intermediate layer being made of the film according to claim 5.

Citation Information

Patent Citations

  • Readily peelable film and double film packaging bag using the same

    JP2007022012A

  • Resin composition and formed film thereof

    JP2011140593A

  • Lid material and package

    JP2013233951A

  • Multilayered sealant film

    JP2015120249A

  • Resin composition and applications thereof

    JP2019123842A